The kinesin Kif21b binds myosin Va and mediates changes in actin dynamics underlying homeostatic synaptic downscaling - Kira V. Gromova; Edda Thies; Philipp C. Janiesch; Felix P. Lützenkirchen; Yipeng Zhu; Daniele Stajano; Céline D. Dürst; Michaela Schweizer; Anja Konietzny; Marina Mikhaylova; Christine E. Gee; Matthias Kneussel (Cell Reports, 2023)
Summary: Homeostatic synaptic plasticity adjusts the strength of synapses to restrain neuronal activity within a physiological range. Postsynaptic guanylate kinase-associated protein (GKAP) controls the bidirectional synaptic scaling of AMPA receptors (AMPARs); however, mechanisms by which chronic activity triggers cytoskeletal remodeling to downscale synaptic transmission are barely understood. Here, we report that the microtubule-dependent kinesin motor Kif21b binds GKAP and likewise is located in dendritic spines in a myosin Va- and neuronal-activity-dependent manner. Kif21b depletion unexpectedly alters actin dynamics in spines, and adaptation of actin turnover following chronic activity is lost in Kif21b-knockout neurons. Consistent with a role of the kinesin in regulating actin dynamics, Kif21b overexpression promotes actin polymerization. Moreover, Kif21b controls GKAP removal from spines and the decrease of GluA2-containing AMPARs from the neuronal surface, thereby inducing homeostatic synaptic downscaling. Our data highlight a critical role of Kif21b at the synaptic actin cytoskeleton underlying homeostatic scaling of neuronal firing.